Pengaplikasian Konsep Peubah Acak dalam Mengukur Kemampuan Representasi Matematis Mahasiswa - Nayla Desviona; Ermaini Ermaini; Muhammad Ikhsan; Nazaruddin Nazaruddin; Sabrina Sabrina; Zul Fanji (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
The distribution of probability, also known as the distribution of random variables, is a part of the Statistics course material. This study aims to describe the mathematical representation skills of students on the topic of probability distribution, based on the fact that many students struggle to understand this material. This study uses a descriptive method. The subjects of this research are 12 students from Muhammadiyah University of Jambi. Data in this study were collected through written tests. The data were analyzed quantitatively and descriptively. The results of the study indicate that students' abilities to work on probability distribution material are still considered low. Therefore, there is a need for teaching methods that can help students understand better and achieve better results.